ANTIVIRAL IL-33-STUMULATED GROUP 2 INNATE LYMPHOID CELLS (CD-90 AND CD-117) FROM MOUSE LUNGS - Khaidarov, S. (Eurasian Journal of Applied Biotechnology, 2024)
This article represents not only a significant scientific value, but also a great teaching and instruction value for researchers and motivated students to improve the skill spectrum in flow cytometry. This article provides step-by- step procedure description and results based on in vivo studies on murine lung tissue, cell of interest isolation with dual protocols for flow cytometry method as well as IL-33 impact in dynamics. The newly described innate lymphoid cells of group 2 (ILC2) play an important role in type 2 immune reactions, epithelial repair in mucosal tissue and metabolic homeostasis. ILC2 releases large amounts of type 2 cytokines such as interleukin 4 (IL-4), IL-5 and IL-13, which stimulate type 2 immunity, such as protection against worms. However, without strict regulation, the level of ILC2 can cause undesirable type 2 immune pathologies, including allergic inflammation of the respiratory tract, hypersensitivity of the respiratory tract and atopic dermatitis. Viral infections of the respiratory tract, which are typical triggers of type 1 immune reactions, often lead to type 2 pulmonary immune pathologies, such as asthma and its exacerbations. Interestingly, pulmonary virus infections induce the release of IL-33 with subsequent induction of ILC2-mediated type 2 pulmonary immunopathology, which is independent of the adaptive immune system.